Evaluation of Left Atrial Functions by 2‐dimensional Speckle‐Tracking Echocardiography During Healthy Pregnancy. (29th March 2019) - Tasar, Onur; Kocabay, Gonenc; Karagoz, Ali; Kalayci Karabay, Arzu; Karabay, Can Yucel; Kalkan, Sedat; Kirma, Cevat
Abstract : Objectives: We aimed to determine the effects of normal pregnancy on left atrial (LA) mechanics using 2‐dimensional speckle‐tracking echocardiography. Methods: A total of 47 healthy women with singleton pregnancies were prospectively enrolled in this study. A total of 4 visits, including each trimester and postpartum at 6 months, were planned. Echocardiographic studies were performed with a Vivid 7 device equipped with a 2.5‐MHz transducer (GE Vingmed Ultrasound AS, Horten, Norway). Results: Although the LA reservoir phase strain showed a gradual decrease from the first trimester to the third trimester during pregnancy, the measurements in the postpartum period were found to return to initial levels (mean ± SD: first trimester, 40.3% ± 11.7%; second trimester, 37.5% ± 12.9%; third trimester, 33.5% ± 9.0%; postpartum, 42.1% ± 11.1%; P < .001). The LA pump function strain was also parallel to the LA reservoir strain and gradually decreased from the first trimester to the third trimester during pregnancy, and it was observed that rose to the initial level in the postpartum period (first trimester, 16.7% ± 7.4%; second trimester, 14.8% ± 5.5%; third trimester, 12.7% ± 4.3%; postpartum, 15.8% ± 5.5%; P < .001). Conclusions: We prospectively determined normal reference values for LA deformation parameters using speckle‐tracking echocardiography in each trimester and the postpartum period in healthy pregnancy. These reference values may help identify subclinical LA dysfunction in several cardiovascular or systemic conditions. According to this study, these parameters decreased toward the third trimester during pregnancy and recovered in the postpartum period.